2013
DOI: 10.1016/j.cmet.2013.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Pitfalls of CNS Cre-Based Technology

Abstract: Nestin-Cre mice have a significant metabolic phenotype that is hard to discern from current literature. Indeed, the Cre-lox system has numerous problems that can affect physiological parameters, and these are missed when the correct control strains are not used. Despite the increasing use of the Cre-lox system, these issues were not visible to the scientific community previously and may have affected published work. This makes it important to highlight the issues and raise awareness of the pitfalls of the Cre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
168
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(172 citation statements)
references
References 64 publications
2
168
1
1
Order By: Relevance
“…It is key to point out that, in addition to mediating recombination of floxed alleles in POMC neurons of the hypothalamus, Pomc-Cre lines also mediate recombination in extra-hypothalamic POMC-neurons and in some non-POMC neurons in adults (27). This limitation is inherent to most developmental Cre lines presently used by most research groups (13,25,30). Thus, it is possible that the phenotype reported here could be related to unspecific recombination of the CAAGS Lox-stop-LoxDeptor allele.…”
Section: Discussionmentioning
confidence: 99%
“…It is key to point out that, in addition to mediating recombination of floxed alleles in POMC neurons of the hypothalamus, Pomc-Cre lines also mediate recombination in extra-hypothalamic POMC-neurons and in some non-POMC neurons in adults (27). This limitation is inherent to most developmental Cre lines presently used by most research groups (13,25,30). Thus, it is possible that the phenotype reported here could be related to unspecific recombination of the CAAGS Lox-stop-LoxDeptor allele.…”
Section: Discussionmentioning
confidence: 99%
“…This protective effect against HFD feeding was not observed in mice that were heterozygous for CNS-specific Tak1 deletion (Tak1 flox/+ NestinCre) (Fig. S3F), demonstrating that expression of Nestin-Cre alone did not cause observable effects under our experimental settings, although an earlier study reported a marginal reduction in weight gain upon Nestin-Cre expression (Harno et al, 2013). Thus, CNS-specific Tak1 deletion is the cause of resistance to HFD-induced excessive weight gain.…”
Section: Tak1 Deficiency Increases Er Volumementioning
confidence: 49%
“…The effect of the GLP-1 mimetic on islet cell composition is reproduced by the DPP4i, albeit at a slower pace indicating that beta cell ablation is correlated with the concentration of the incretin in the circulation. These observations add to previously raised concerns regarding the toxic effects of Cre on cell function (1,3,4,30) and highlight the need for caution in the interpretation of results using the Cre-lox technology.…”
Section: Discussionmentioning
confidence: 87%
“…It has been proposed that the physiological abnormalities of transgenic RIP-Cre mice may be avoided using an inducible form of Cre (1,3,4). Although the efficiency of recombination is lower than in lines with constitutive Cre expression, the possibility was raised that the appearance of metabolic abnormalities would be evaded with the lower levels of recombinase.…”
mentioning
confidence: 99%